(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
Bioluminescent imaging (BLI) is a non-invasive and sensitive method for tracking tumor growth, based on the luciferase reaction. It is used to assess tumor size and evaluate treatment efficacy. However, the accuracy of BLI is influenced by factors such as substrate distribution, transport, and clearance. This study analyzes the key factors that impact the effectiveness of BLI in preclinical models of breast cancer.